Philosophical ideas of Roger Williams in the treatise “A Key into the Language of America” - Yaroslav Sobolievskyi (Future Human Image, 2019)
Philosophical views of the American thinker Roger Williams on the nature of man, his rights and obligations are described in the article. Thinker’s philosophical views were determined by a number of strong political ideas, in particular — secularism; religious nature, namely, tolerance and Baptism; and humanistic, namely abolitionism. Particular attention is paid to the relationship between settlers and indigenous people on language issues. He lived and worked in the colony of Rhode Island, founded by him in 1636, today the official name is the State of Rhode Island and the Providence Plantation. History shows that after he was expelled from the colony of the Massachusetts Bay due to the conflict of religious views, Roger Williams settled at Narragansett Bay, calling this place Providence. This colony became a haven for many pilgrims from religious persecution. The Puritans treated the indigenous people extremely negatively, the Quakers differed with their peace-loving views, and the Catholics carried the word of God. During the preaching of Christianity among the Indians, the Jesuits, unlike the Puritans, did not force the Indians to wear European clothing and used methods that emphasized respect for the traditions of the culture of the indigenous people. In 1643, Roger Williams wrote the book “A Key into the Language of America” (the full name is “A help to the Language of the Natives in that part of America called New England”). He described the language of the 17th century Indians, namely Algonquian language. This book was the first study of the language of the Indians, but in addition to the language itself, the thinker analyzed many philosophical ideas. The philosophical ideas of the treatise are explored in this article